Manajemen Peserta Didik Anak Berkebutuhan Khusus Melalui Pendekatan Lingkungan Inklusi Ramah Pembelajaran (LIRP) Pada Sekolah Dasar Reguler - Maria Yulianti Goo (Jurnal Pelayanan Pastoral, 2020)
The purpose of compiling this article is to describe the management of students with special needs by using a qualitative descriptive method through literature review, observation and interviews in the field with inclusion in school education. Through literature review to see theories and be used as a reference source. The observation intended by the author made direct observations in the field while the interview, the author conducted interviews to explore and obtain information from reliable informants related to the implementation of management of students with special needs with an inclusive and friendly learning approach in regular elementary schools. The results obtained that the management of students with special needs with a friendly learning inclusion environment approach is a process in empowering existing human resources in the school as the subject of education, where all these educational actors empower themselves through the process of social interaction, with the aim of honing effective sensitivity and cognitive intelligence. Thus a regular primary school that is included is a means to create an environment for the development of all aspects of the lives of students with special needs and other educational actors more optimally. From the results of this study, one recommendation is a note for policy makers and providers of inclusive education to provide adequate resources for services for children with special needs such as medical workers, psychologists, doctors and placed in inclusion in regular schools.